Comentario del poema Ad Bacchum de José de Acosta - Izquierdo Izquierdo, José Antonio; Martínez Ortega, Ricardo (1992)
This paper analyses, from a formal point of view, José Acosta's Latin poem Ad Bacchum. We have payed attention to the micro-structure of the text and its macro-structure, and no difference from the classic canon can be observed. We think that a didactic pupose can be inferred from the inclusion of footnotes explaining the meaning of some words.
Keywords: Acosta, José de